Smoking, Alcohol, and Biliary Tract Cancer Risk: A Pooling Project of 26 Prospective Studies. (25th May 2019) - McGee, Emma E; Jackson, Sarah S; Petrick, Jessica L; Van Dyke, Alison L; Adami, Hans-Olov; Albanes, Demetrius; Andreotti, Gabriella; Beane-Freeman, Laura E; Berrington de Gonzalez, Amy; Buring, Julie E; Chan, Andrew T; Chen, Yu; et al.
Abstract: Background: Tobacco and alcohol are well-established risk factors for numerous cancers, yet their relationship to biliary tract cancers remains unclear. Methods: We pooled data from 26 prospective studies to evaluate associations of cigarette smoking and alcohol consumption with biliary tract cancer risk. Study-specific hazard ratios (HRs) and 95% confidence intervals (CIs) for associations with smoking and alcohol consumption were calculated. Random-effects meta-analysis produced summary estimates. All statistical tests were two-sided. Results: Over a period of 38 369 156 person-years of follow-up, 1391 gallbladder, 758 intrahepatic bile duct, 1208 extrahepatic bile duct, and 623 ampulla of Vater cancer cases were identified. Ever, former, and current smoking were associated with increased extrahepatic bile duct and ampulla of Vater cancers risk (eg, current vs never smokers HR = 1.69, 95% CI = 1.34 to 2.13 and 2.22, 95% CI = 1.69 to 2.92, respectively), with dose-response effects for smoking pack-years, duration, and intensity (all P trend  < .01). Current smoking and smoking intensity were also associated with intrahepatic bile duct cancer (eg, >40 cigarettes per day vs never smokers HR = 2.15, 95 % CI = 1.15 to 4.00; P trend  = .001). No convincing association was observed between smoking and gallbladder cancer. Alcohol consumption was only associated with intrahepatic bile duct cancer, with increased risk for individuals consuming five or more vs zero drinks per day (HR = 2.35, 95%CI = 1.46 to 3.78; P trend  = .04). There was evidence of statistical heterogeneity among several cancer sites, particularly between gallbladder cancer and the other biliary tract cancers. Conclusions: Smoking appears to increase the risk of developing all biliary tract cancers except gallbladder cancer. Alcohol may increase the risk of intrahepatic bile duct cancer. Findings highlight etiologic heterogeneity across the biliary tract.